Using YouTube as EFL/ESL Tertiary Students’ Self-English Language Learning Strategies - Dedi Aprianto (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Today, the use of Technology in the forms of internet-based video media, YouTube, is considered as the complementary, supporting, and effective learning media in English Language Learning. YouTube as the mostly and broadly-used social media, online video service, present the appropriate solutions dealing with the educational issues in the forms of rich, creative, and ground-breaking language learning strategies. The current study aims at knowing the dominant language skills and language components the tertiary students learn through YouTube and to investigate the why they used YouTube flatform as their Self-Language Learning Strategies. It used the descriptive qualitative study to describe the usages of YouTube as language learning media and to know the dominant types of language skills and language components always fostered through YouTube from the numerical data which is needed to be descriptively-statistical analized. The data was obtained through questionnaire and semi-structured interview by involving 35 the sophomore students of computer science. The results suggest that of the four English skills, the tertiary students mostly used YouTube to individually study or to improve listening (90%), speaking (81%), writing (47%), reading (59%). The receptive skills are more dominant than the productive skills. The tertiary students dominantly used YouTube as self-learning strategy to improve their language components, that is studying pronunciation (79%), Grammars (74%), vocabulary (71%). The EFL/ESL tertiary students used YouTube to individually study English as they believed that YouTube learning media as the complementary language learning sources, YouTube as the mostly-accessable language learning sources, and YouTube as the innovative self strategies to study more about language skills and language componenets.